Sources of Growth Methodology in Low-Income Countries: A Critique - Kelley, Allen C.; Williamson, Jeffrey G. (Quarterly Journal of Economics, 1973)
I. Introduction, 138. — II. A general equilibrium model of the growing low-income economy, 139. — III. The sources of growth paradox, 141. — IV. An analysis of the sources of growth paradox, 144. — V. Conclusion, 147.